Pengaruh E-Modul Berbasis Guided Discovery Terhadap Pengetahuan Faktual, Konseptual, dan Prosedural pada Pembelajaran IPA Kelas V - Rahayu, Anisa; Widi Winarni, Endang; Koto, Irwan (UNIB Press, 2024)
This study aims to analyze the effect of guided discovery-based e-modules on the mastery of factual, contextual and procedural knowledge of